2017
DOI: 10.1016/j.seizure.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of alcohol dependency in deaths among people with epilepsy recorded by the National Drug-Related Deaths Index (NDRDI) in Ireland, 2004–2013

Abstract: The high percentage of individuals with a diagnosis of alcohol dependency that died as a result of epilepsy and who have no antiepileptic drugs in their system at the time of their death, highlights the need for preventative measures for this at-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Other studies have reported the proportion or likelihood of alcohol involvement in death among persons with epilepsy. The National Drug-Related Deaths Index of Ireland is a surveillance system that records all causes of death in people who are dependent on alcohol or drugs, or die due to poisoning (21). Two percent of individuals in this register were known to have epilepsy and 81% of these had a history of alcohol dependence prior to death.…”
Section: Discussion Elevated Risk Of Alcohol-specific Deathmentioning
confidence: 99%
“…Other studies have reported the proportion or likelihood of alcohol involvement in death among persons with epilepsy. The National Drug-Related Deaths Index of Ireland is a surveillance system that records all causes of death in people who are dependent on alcohol or drugs, or die due to poisoning (21). Two percent of individuals in this register were known to have epilepsy and 81% of these had a history of alcohol dependence prior to death.…”
Section: Discussion Elevated Risk Of Alcohol-specific Deathmentioning
confidence: 99%
“…According to a study by Lynn et al (48), between 2004 and 2013, 225 (2%) of registered cases had a documented history of epilepsy, of which 82 (36%) recorded epilepsy as the cause of death. Of these 82 deaths, the majority were male (60-73%) and for half of them the median age was 47 years or younger.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Substance abuse may increase the risk of poorly controlled epilepsy, as both alcohol and drug use may worsen seizures. Patients with epilepsy and alcohol dependence are at an increased risk of medication noncompliance, increasing the possibility of epilepsy‐related death …”
Section: Social Issuesmentioning
confidence: 99%
“…Patients with epilepsy and alcohol dependence are at an increased risk of medication noncompliance, increasing the possibility of epilepsy-related death. 32 Some transgender persons cannot or do not seek traditional health care for gender-affirming treatment, and a substantial percentage may purchase hormones from nonmedical sources, 33 such as websites or untrained providers. These products may not have the level of oversight and quality control of medical sources of hormones, and patients may be at risk for seizure exacerbation if using impure or adulterated products.…”
Section: Social Issuesmentioning
confidence: 99%